Surface‐enhanced Raman spectroscopy in art and archaeology. (29th October 2015) - Pozzi, Federica; Leona, Marco
Abstract : Since its introduction in the cultural heritage field, nearly 30 years ago, surface‐enhanced Raman spectroscopy (SERS) has emerged as a promising analytical technique that is particularly suitable for the detection and identification of organic colorants. Its great molecular selectivity and specificity, and unparalleled sensitivity compared to other instrumental methods, have allowed researchers to successfully characterize a wide number of natural dyes and a few synthetic ones in microscopic samples from objects of artistic, historical, and archaeological significance. Continued research over the course of the past decade has led to the construction of comprehensive databases of dyes, whose adsorption and spectral properties have been investigated at length; to the comparative study of the efficiency and performance of various metal substrates; and to the evaluation of several sample treatment methods and ad‐hoc analytical protocols. In addition, recent literature in the field of SERS for art and archaeology has described instrumentation and technique advancements aimed at solving the unique challenges posed by the analysis of irreplaceable objects, namely, quasi non‐destructive sampling, spatial resolution improvement, examination of insoluble compounds, and resolution of dye mixtures. Reviewing the most salient methodological and technological milestones that have traced the history of SERS for cultural heritage to date, the present article is intended as a practical resource for those researchers who would like to undertake systematic characterization of organic colorants from artworks using this powerful technique. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Over nearly three decades, surface‐enhanced Raman spectroscopy (SERS) has been used to detect and identify organic colorants from objects of artistic, historical and archaeological significance. While reviewing the most relevant analytical protocols, methodological and technological advancements that have made SERS a truly fundamental resource in the field of cultural heritage, this article aims to provide researchers who intend to undertake the characterization of dyes using this technique with a solid bulk of basic knowledge and examples from real‐world applications.